1995
DOI: 10.1111/j.1095-8649.1995.tb05942.x
|View full text |Cite
|
Sign up to set email alerts
|

Migratory behaviour of wild and farmed Atlantic salmon (Salmo salar) during spawning

Abstract: Migratory behaviour at spawning of wild and newly-escaped farmed Atlantic salmon was analysed by radio telemetry in the River Alta, North Norway. Spawning areas were located by aerial surveys. Farmed females moved significantly more than wild females (PcO.01). There was no such difference between the two groups of males. About 83% of the wild fish stayed within identified spawning areas for 1 day or longer. The corresponding figure for farmed salmon was only 43'%, (P<0.05). Wild salmon stayed 8.1 days inside s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 16 publications
1
38
0
Order By: Relevance
“…Studies that have examined the interaction of wild and escaped farmed salmon occasionally report that farmed fish enter the rivers later (Gausen and Moen, 1991), tend to spawn more in the lower reaches of a river, and later in the year (Webb et al, 1991) than wild salmon although this is not consistent among all studies (Okland et al, 1995). In our experiment, the first group was released to coincide with the timing of the natural salmon return to Conne River, but the cage-reared wild fish generally delayed their return to the river for several weeks.…”
Section: Discussionmentioning
confidence: 98%
“…Studies that have examined the interaction of wild and escaped farmed salmon occasionally report that farmed fish enter the rivers later (Gausen and Moen, 1991), tend to spawn more in the lower reaches of a river, and later in the year (Webb et al, 1991) than wild salmon although this is not consistent among all studies (Okland et al, 1995). In our experiment, the first group was released to coincide with the timing of the natural salmon return to Conne River, but the cage-reared wild fish generally delayed their return to the river for several weeks.…”
Section: Discussionmentioning
confidence: 98%
“…No erratic movement pattern was found in farmed compared to wild salmon during the upstream migration phase (Heggberget et al 1996), but the farmed fish showed more and longer up-and downstream movements during the spawning period (Økland et al 1995;. Despite a tendency for farmed salmon being distributed higher up in the river during spawning, wild and farmed salmon were not geographically separated, and farmed fish occurred in parts of the river with important wild salmon spawning areas (Heggberget et al 1996;Butler et al 2005).…”
Section: Previous Experiencementioning
confidence: 92%
“…Cultured Atlantic salmon enter rivers to spawn later in the season, move about more, and stay in the river for a shorter time than wild fish (Jonsson et al, 1990;Økland et al, 1995). That cultured fish are not homing to any particular spawning area, probably influences upstream migration.…”
Section: Spawningmentioning
confidence: 99%
“…;Riley et al, 2005 River movement B Jonsson et al, 1990;Økland et al, 1995 . River stay B. Jonsson et al, 1990 Straying to foreign riversHansen et al, 1993; B. Jonsson et al, 2003 Predator recognition Brown andSmith, 1998;Mirza and Chivers, 2000;Berejikian et al, 2003b; Vilhunen et al, 2005 Refuge use Griffiths andOrpwood et al, 2004Rungruangsak-Torrissen et al, 1998; N. Jonsson et al, 2005 Protein synthesis Rungruangsak-Torrissen et al, 1998, 1999 Maintenance ration Rungruangsak-Torrissen et al, 1998, 1999 Youngson and Webb, 1992; McCormick et al, 2003 Adiposy Rowe et al, 1991; Silverstein et al, 1999 Maturity age Patterson et al, 2004 Swimming performance McDonald et al, 1998; Claireaux et al, 2005 Fin healing Jørgensen and Jobling, 1993…”
mentioning
confidence: 99%